Retransplantation After Living Donor Liver Transplantation: Data from the Adult to Adult Living Donor Liver Transplantation Study. Issue 6 (June 2021) - Braun, Hillary J.; Grab, Joshua D.; Dodge, Jennifer L.; Syed, Shareef M.; Roll, Garrett R.; Schwab, Marisa P.; Liu, Iris H.; Glencer, Alexa C.; Freise, Chris E.; Roberts, John P.; Ascher, Nancy L.
Abstract : Background: The use of living donor liver transplantation (LDLT) for primary liver transplantation (LT) may quell concerns about allocating deceased donor organs if the need for retransplantation (re-LT) arises because the primary LT did not draw from the limited organ pool. However, outcomes of re-LT after LDLT are poorly studied. The purpose of this study was to analyze the Adult to Adult Living Donor Liver Transplantation Study (A2ALL) data to report outcomes of re-LT after LDLT, with a focus on long-term survival after re-LT. Methods: A retrospective review of A2ALL data collected between 1998 and 2014 was performed. Patients were excluded if they received a deceased donor LT. Demographic data, postoperative outcomes and complications, graft and patient survival, and predictors of re-LT and patient survival were assessed. Results: Of the 1065 patients who underwent LDLT during the study time period, 110 recipients (10.3%) required re-LT. In multivariable analyses, hepatitis C virus, longer length of stay at LDLT, hepatic artery thrombosis, biliary stricture, infection, and disease recurrence were associated with an increased risk of re-LT. Patient survival among re-LT patients was significantly inferior to those who underwent primary transplant only at 1 (86% versus 92%), 5 (64% versus 82%), and 10 years (44% versus 68%). Conclusions: Approximately 10% of A2ALL patients who underwent primary LDLT required re-LT. Compared with patients who underwent primary LT, survival among re-LT recipients was worse at 1, 5, and 10 years after LT, and re-LT was associated with a significantly increased risk of death in multivariable modeling (hazard ratios, 2.29; P < 0.001).